Genetics A Conceptual Approach - Pierce, Benjamin A. (W.H. Freeman, 2012)
Identifying the key concepts and making connections among them, Pierce allows students to study the big picture of genetics. The 4th edition includes new coverage on epigenetics, the first synthetic organism, our relationship to Neanderthals, microRNAs, and updates to numbers, structures, and mechanisms.